LEVEL OF EXPRESSION OF MICRORNA IN PLACENTA AT ANTENATAL FETAL DEATH AND LIVE BIRTH AT FULL TERM OF PREGNANCY - Евгений Леонидович Казачков; Элла Алексеевна Казачкова; Анна Валерьевна Чижовская; Юлия Андреевна Веряскина; Юрий Алексеевич Семенов; Наталья Валентиновна Жарова; Алексей Юрьевич Семенов (The Publishing House Medicine and Enlightenment, 2024)
At present, much attention is focused on the placental formation process and the mechanisms that influence or regulate it. It is evident that disruption of the process, especially in early stages of development, leads to structural and functional defects of the placenta. This, in turn, leads to pregnancy complications such as preeclampsia, fetal growth retardation, premature births and negative perinatal outcomes. One of the main mechanisms regulating placenta formation and development is genetic. Epigenetic structures, such as miRNAs, control gene expression without altering the DNA sequence, and considered to be the primary pathogenesis of placental insufficiency and the associated complications of pregnancy. MiRNA are small RNA molecules (up to 25 nucleotides) transcribed with genomic DNA and exported to cytoplasm cells. Several thousand miRNAs are encoded in the human genome, representing a regulatory network that acts on cellular processes through various signaling pathways. MiRNA disorders lead to a wide range of diseases, including pregnancy complications. The study of changes in miRNA expression levels involved in the regulation of placental formation and growth is necessary to understand thanatogenesis of one of the most difficult-to-predict complications of pregnancy - antenatal death of the full-term fetus. The aim of the research. Conduct a comparative analysis of the level of expression of a number of miRNAs in the placenta of patients with antenatal fetal death and live birth in the outcome of timely delivery. Materials and methods. A molecular biological study of placental tissue samples from 60 patients was conducted: 30 patients with antenatal fetal death (Group A) and 30 patients with a live birth in pre-term pregnancy (Group B). Consistently, tissue samples were dewaxed, RNA extraction, reverse transcription reaction and polymerase chain reaction (PCR) were carried out in real time. A comparative analysis of the expression level of 18 microRNAs was studied and carried out: -21, -23a, -26a, -29b, -31, -100, -125b, -126, -128, -150, -191, -204, -221, - 223, -451, -1246, -let7a, -U6. Results. Mostly antenatal death of the full-term fetus was accompanied by signs of chronic placental insufficiency and hypoxic damage to the stromal-vascular placental part. There has been a statistically significant decrease in GLUT-1 expression and an increase in HIF-1α and CASP-3 expression in placenta of patients with antenatal fetal death in full-term pregnancy. Conclusion. Thus, changes in microRNA-126, -29b, -21, -26a, -100, and let-7a have been shown to disrupt the processes of apoptosis and immune response in placental cells, which are essential in antenatal fetal death at the full-term of pregnancy.